Aesthetic Engagement with Mouse Bird Snake Wolf – Literary Multimodal Literacy in English Language Education - Mari Skjerdal Lysne (CLELEjournal, 2023)
With this paper, Lysne argues for a new kind of literacy she terms literary multimodal literacy, a competence she deems is prerequisite for an engagement with texts like Almond’s hybrid multimodal books for young readers.